2015
DOI: 10.1186/s12958-015-0132-y
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of TIMP-1 in Human Placenta and Fetal Membranes by lipopolysaccharide and demethylating agent 5-aza-2'-deoxycytidine

Abstract: BackgroundAn appropriate transcriptional profile in the placenta and fetal membranes is required for successful pregnancy; any variations may lead to inappropriate timing of birth. Epigenetic regulation through reversible modification of chromatin has emerged as a fundamental mechanism for the control of gene expression in a range of biological systems and can be modified by pharmacological intervention, thus providing novel therapeutic avenues. TIMP-1 is an endogenous inhibitor of MMPs, and hence is intimatel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 75 publications
(71 reference statements)
0
12
0
Order By: Relevance
“…These findings indicate that TIMP-1 expression might be linked to more aggressive subtypes of breast cancer and are consistent with previous studies reporting that TIMP-1 expression is associated with a poor prognosis in breast cancer [ 40 ], colorectal cancer [ 41 ], laryngeal squamous cell carcinoma [ 42 ] and hepatocellular carcinoma [ 43 ]. An increase in TIMP-1 mRNA levels induced by 5-Aza treatment has also been observed in melanoma [ 44 ] and gestational tissues [ 45 ], indicating that promoter methylation mediates the expression of TIMP-1 in various cell types.…”
Section: Discussionmentioning
confidence: 95%
“…These findings indicate that TIMP-1 expression might be linked to more aggressive subtypes of breast cancer and are consistent with previous studies reporting that TIMP-1 expression is associated with a poor prognosis in breast cancer [ 40 ], colorectal cancer [ 41 ], laryngeal squamous cell carcinoma [ 42 ] and hepatocellular carcinoma [ 43 ]. An increase in TIMP-1 mRNA levels induced by 5-Aza treatment has also been observed in melanoma [ 44 ] and gestational tissues [ 45 ], indicating that promoter methylation mediates the expression of TIMP-1 in various cell types.…”
Section: Discussionmentioning
confidence: 95%
“…TIMP1 is an important regulator for both testicular development and spermatogenesis [49]. TIMP1 was highly expressed in ZIKVinfected endothelial cells [50], is intimately involved in maintaining fetal membrane integrity until labor [51], and amniotic fluid levels decrease during pregnancy with advancing gestation [52]. Coordinated regulation of MMPs and TIMPs are required to maintain tissue architecture and normal ovarian function [53,54].…”
Section: Zikv Disrupts Proteins Involved In Hserc Functions Related Tmentioning
confidence: 99%
“…In 2015, the first biochemical evidence that the fetal membranes might be stronger in female pregnancies was published and has provided critical insight into the sex‐specific mechanisms of P‐PROM in human pregnancies . Vincent et al.…”
Section: Maintenance and Rupture Of The Fetal Membranesmentioning
confidence: 99%
“…47 In 2015, the first biochemical evidence that the fetal membranes might be stronger in female pregnancies was published and has provided critical insight into the sex-specific mechanisms of P-PROM in human pregnancies. 49 Vincent et al showed that there is sex-specific expression of tissue inhibitor of metalloproteinase-1 (TIMP-1), an inhibitor of MMPs, and a marker of fetal membrane integrity in amniochorion, where TIMP-1 expression is greater in female amnion at term and is reduced during labour. 49…”
Section: Maintenance and Rupture Of The Fetal Membranesmentioning
confidence: 99%